Adventures with Lex: The gamification of research? - Barwick, Joanna and Watkins, Dawn and Kirk, Elee and Law, Effie (Convergence: The International Journal of Research into New Media Technologies, 2018)
There is a wide range of interest in gamification – with game design elements being used in an increasing number of non-game contexts. Yet, despite these developments, there has been little interest from the academic community in the potential opportunities that gamification presents in the research context. Law in Children’s Lives is an innovative project that has explored the use of a specially designed tablet-based game, Adventures with Lex, as a data collection tool. The game, developed using participatory design techniques, has been used as a means to investigate children’s perceptions of the law in their everyday lives. This article presents a case study of the processes and challenges involved in the development of the game which leads to a discussion of the implications of this study for the wider use of game-based research.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzU0ODU2NTE2Njc3Njgy